1988
DOI: 10.1159/000309924
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Outcome of Prednisone Medication and of Orbital Irradiation in Patients with Graves’ Ophthalmopathy

Abstract: Response to treatment was evaluated prospectively in 58 patients with Graves’ ophthalmopathy. Prednisone, administered to 44 patients, resulted in a favourable response in 29 patients (66%): excellent in 3, good in 10 and fair in 16 subjects; 15 patients (34%) did not respond. Orbital irradiation was administered to 39 patients of whom all except 4 had been treated previously with steroids. Six months later, 25 patients (64%) had responded favourably (excellent in 0, good in 9 and fair in 16 subjects) and 14 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…However, the mechanism by which DEX reduces the relapse rate of GD is not fully understood. DEX is a kind of glucocorticoid usually used in the treatment of Graves' ophthalmopathy (GO) and is one of the most effective medicines (14,15). Some reports showed that Treg cell count increased with DEX treatment in chronic idiopathic thrombocytopenic purpura and other autoimmune diseases (16,17).…”
Section: Cd25mentioning
confidence: 99%
“…However, the mechanism by which DEX reduces the relapse rate of GD is not fully understood. DEX is a kind of glucocorticoid usually used in the treatment of Graves' ophthalmopathy (GO) and is one of the most effective medicines (14,15). Some reports showed that Treg cell count increased with DEX treatment in chronic idiopathic thrombocytopenic purpura and other autoimmune diseases (16,17).…”
Section: Cd25mentioning
confidence: 99%
“…Having reached the final stage, structural and functional changes are refractory to anti-inflammatory treatment and thus irreversible (Wiersinga et al 1988;Mourits et al 1989;Prummel et al 1993). To avoid irreversible changes such as motility disturbances with diplopia and exophthalmos with potential corneal damage, it is important to initiate anti-inflammatory treatment prior to the irreversible stage.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered to be an organ-specific autoimmune disease, but it is uncertain whether cellular or humoral immunological mechanisms are primarily disturbed [13]. Corticosteroids are the mainstay of itntnunosuppresslve treatment, to which about 65'^.. of patients respond [14,15], The factors determining the response are unknown, but it is conceivable that a favourable response is associated with the activity of the autoimmune process [16]. To .spare patients with inactive eye disease the side-effects of prednisone.…”
Section: Introductionmentioning
confidence: 99%